2000
DOI: 10.1037/0735-7044.114.2.353
|View full text |Cite
|
Sign up to set email alerts
|

The suppressive effects of sucrose and cocaine, but not lithium chloride, are greater in Lewis than in Fischer rats: Evidence for the reward comparison hypothesis.

Abstract: Rats suppress intake of a saccharin conditioned stimulus (CS) when it is paired with an aversive unconditioned stimulus (US), an appetitive US, or a drug of abuse such as morphine or cocaine. It is unclear, however, whether the reduction in intake induced by these drugs is mediated by their aversive or their rewarding properties. The present set of experiments addressed this question by comparing the suppressive effects of a known aversive US (LiCl), a known reinforcing US (sucrose), and a drug of abuse (cocai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
90
4

Year Published

2000
2000
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(101 citation statements)
references
References 69 publications
(121 reference statements)
7
90
4
Order By: Relevance
“…In this interpretation, the sucrose becomes a conditioned stimulus predicting the forthcoming presentation of the more rewarding amphetamine. This effect, called the anticipatory contrast effect, is observed when saccharin is paired with drugs of abuse or when a weaker saccharin solution is paired with a subsequent stronger solution (Grigson and Freet 2000;Schroy et al 2005). Additional support comes from the observation that ibotenic acid lesions of the gustatory thalamus disrupt the avoidance of the saccharin produced by injection of drugs of abuse, but not by injection of lithium chloride (Grigson and Freet 2000;Schroy et al 2005;Reilly et al 2004).…”
Section: Discussionmentioning
confidence: 72%
See 2 more Smart Citations
“…In this interpretation, the sucrose becomes a conditioned stimulus predicting the forthcoming presentation of the more rewarding amphetamine. This effect, called the anticipatory contrast effect, is observed when saccharin is paired with drugs of abuse or when a weaker saccharin solution is paired with a subsequent stronger solution (Grigson and Freet 2000;Schroy et al 2005). Additional support comes from the observation that ibotenic acid lesions of the gustatory thalamus disrupt the avoidance of the saccharin produced by injection of drugs of abuse, but not by injection of lithium chloride (Grigson and Freet 2000;Schroy et al 2005;Reilly et al 2004).…”
Section: Discussionmentioning
confidence: 72%
“…It is possible that adult and old F-344 rats respond differently to sucrose than do Wistar rats. While strain differences have been reported in the acquisition of a CTA, these studies have used young rats and the differences that are observed are on the effects of specific stimuli and manipulations on CTA learning (Grigson and Freet 2000;Foynes and Riley 2004;Kosten et al 1994;Lancellotti et al 2001).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In accordance with this prediction, the suppressive effects of drugs of abuse and sucrose, but not those of LiCl, are greatly attenuated by food and water deprivation [52][53][54][55]. The suppressive effects of cocaine and sucrose, but not LiCl, are greater in drug sensitive Lewis, than less sensitive Fischer, rats [16,56 ]. The suppressive effects of cocaine and sucrose, but not LiCl, are augmented in rats with a history of chronic morphine treatment [57].…”
Section: The Model: Experimenter Delivered Drugmentioning
confidence: 71%
“…It is this positive rewarding drug state, rather than some aversive effect of drugs that are self-administered, that will lead to suppression of intake due to a conditioned "taste shyness." In a similar direction, the resulting taste avoidance may be due to a comparison between the less valued flavor stimulus and the anticipation of a highly valued drug effect when saccharin serves as the CS, as was often (but not always) the case in the reviewed experiments (Grigson and Freet, 2000). Such an interpretation is hard to maintain, however, when one considers that populations such as DBA/2J mice, and selectively bred NP rats and LAP mice, which drink almost no alcohol in the home cage, show robust conditioned taste aversion to ethanol.…”
Section: Discussionmentioning
confidence: 87%